Fibroblasts mediate the angiogenesis of pheochromocytoma by increasing COX4I2 expression - Mao, Yongxin; Zhuo, Ran; Ma, Wenming; Dai, Jun; Alimu, Parehe; Fang, Chen; Xu, Danfeng; Ye, Lei; Wang, Weiqing; Sun, Fukang (Frontiers in Oncology, 2022)
Objective Our previous work found COX4I2 was associated with angiogenesis in pheochromocytoma. The purpose of this study was to explore the role of COX4I2 in regulating angiogenesis in pheochromocytoma. Methods Distribution of COX4I2 was evaluated by scRNA-seq in one case of pheochromocytoma and the findings were verified by immunostaining. COX4I2 was further knocked down in target cells. Changes of angiogenesis-related genes were evaluated by qPCR in target cells. Results The scRNA-seq revealed high mRNA expression of COX4I2 in fibroblasts rather than tumor cells. Immunostaining of COX4I2 confirmed its distribution in fibroblasts. Knocking down COX4I2 in NIH3T3 cell line led to significant reduction of angiogenesis-related genes, especially ANG1 and HGF. Conclusions Fibroblasts mediate the angiogenesis of pheochromocytoma by increasing COX4I2 expression, possibly by affecting ANG1 and HGF.